Chrysin–organogermanium (IV) complex induced Colo205 cell apoptosis‐associated mitochondrial function and anti‐angiogenesis. Issue 4 (23rd April 2015) - Yang, Fen; Gong, Longcai; Jin, Hua; Pi, Jiang; Bai, Haihua; Wang, Hong; Cai, Huaihong; Yang, Peihui; Cai, Jiye
Summary Colorectal cancer, a kind of malignant cancer, has more than 1 million new patients and results in 0.5 million deaths every year globally based on the estimation of Globocan in 2008. One of the most important issues against colon cancer is tumor metastasis. Anti‐angiogenesis, a form of targeted therapy uses drugs or other substances to prevent the new blood vessel formation, which is critical for tumor metastasis. In our previous studies, we have demonstrated a simple method to synthesize Chry–Ge complex through the reaction between chrysin and triphenylgermanium bromide. In this work, we investigated the mechanism of Chry–Ge induced Colo205 cell apoptosis. We found that Chry–Ge could induce apoptosis in Colo205 cells in mitochondrial‐dependent pathway, cause the reorganization of cytoskeleton and induce the damage of nucleus in Colo205 cells. Besides, Chry–Ge was also found to induce membrane ultrastructural changes in Colo205 cells by AFM. Further, we found that Chry–Ge can inhibit tube formation of human umbilical vascular endothelial cell in vitro. Chry–Ge was also tested in vivo in the chicken chorioallantoic membrane (CAM) assay and found to inhibit bFGF‐treated CAMs development. These results suggested that Chry–Ge could induce Colo205 cell apoptosis by mitochondrial pathway and anti‐angiogenesis, highlighting the use of organic germanium agents for the treatment of colorectal cancer. SCANNING 37:246–257, 2015. © 2015 Wiley Periodicals, Inc.